Blindfolded Eyes and the Eyable Being: Pessoa, the senses, and the 35 Sonnets - Santos, M. Irene Ramalho (2016)
This article revisits Pessoa’s heteronymism (as performativity) in relation to the old issue of poetic unity/diversity. It examines Pessoa’s espistemological skepticism, while handling the five senses in the 35 Sonnets, in comparison and contrast with his so-called “obscene poems” and the rest of his poetry.